Voluntary Compliance Program for Taxpayers in the Republic of Moldova - Nadejda BERGHE (ACROSS)
In order to perform the main tasks and objectives, the State Tax Service ensures the permanent examination and identifies the segments of the national economy with increased risk of tax non-compliance, applying the simplest and most effective treatments to mitigate the risks of non-compliance and increase the level of voluntary tax compliance.